Problem Dialog Antariman: Membangun Keberagamaan Inklusif - Zuly Qadir (Millah: Journal of Religious Studies, 2004)
This article describes actual problems on religious dialogue, in actual Indonesia. Several problems in interfaith dialogue, such as contexts of as textual-doctrine, human dialogue, community segmentation in Muslim and Christian, on five years era, praxis and theoretic theology dichotomy, religious prejudice on Muslim and Christian, and then minimum women activities on interfaith dialogue. But, these problems can create encounter dialogue and human dialogue intensively. For alternative solution the problems is religious inclusive.